Marriage Prevention from the Perspective of Maqāṣid al-Sharīʿah: An Analysis of Concealed Marital Status Cases in Temanggung - Mar'atul Ulya; Sumarjoko; Hidayatun Ulfa; Hasman Zhafiri Muhammad (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to analyze a case of marriage prevention resulting from the concealment of marital status by a prospective husband in Kemiri Village, Tembarak District, Temanggung Regency, from the perspective of Maqāṣid al-Sharīʿah. The research employed a qualitative method with a juridical-empirical (field research) approach, using in-depth interviews, observation, and documentation as data collection techniques. The findings reveal that the marriage prevention occurred after it was discovered that the prospective husband was still legally married and intended to engage in polygamy without obtaining the consent of his first wife or authorization from the Religious Court. Such conduct constitutes tadlīs (deception) through the concealment of marital status, which may result in legal, social, and psychological harm to the prospective wife. From the perspective of Maqāṣid al-Sharīʿah, the prevention of this marriage is consistent with the objective of protection at the level of ḍarūriyyāt, particularly in safeguarding lineage (ḥifẓ al-nasl). Legally, the case is classified as marriage prevention prior to the marriage contract (akad nikah), thereby producing no legal consequences of marriage for either party. Sociologically, the involvement of village authorities and religious leaders played a significant role in providing social protection and minimizing stigma toward the woman involved. This study demonstrates that marriage prevention in cases involving the concealment of marital status is not only legally justified but also reflects the implementation of Maqāṣid al-Sharīʿah values in protecting the welfare of individuals and society.